What Links Sleep and Neuropathic Pain?: A Literature Review on the Neural Circuits for Sleep and Pain Control - Ho A; Drew VJ; Kim T (Nature and Science of Sleep)
Anh Ho,1 Victor J Drew,2 Tae Kim1 1Department of Biomedical Science and Engineering, Gwangju Institute of Science and Technology, Gwangju, 61005, Republic of Korea; 2Center for Cognition and Sociality, Institute for Basic Science, Daejeon, 34126, Republic of KoreaCorrespondence: Tae Kim, Gwangju Institute of Science and Technology, 123 Cheomdangwagi-ro, Buk-gu, Gwangju, 61005, Republic of Korea, Email tae-kim@gist.ac.krAbstract: Neuropathic pain (NP), arising from lesions or diseases of the sensory nervous system, significantly disrupts sleep, creating a feedback loop where pain and sleep disturbances exacerbate each other. Research suggests that sleep disruption may contribute to progressing from acute to chronic NP. The neural circuits involved in sleep-wake regulation and pain processing are intricately interconnected, making it difficult to pinpoint the specific regions responsible for each function. This review seeks to disentangle these complex relationships by providing a detailed overview of the anatomical pathways involved in NP, extending from the peripheral to the central nervous system. Additionally, it examines the neurocircuits that govern sleep-wake cycles and their interaction with pain pathways. By illuminating these connections, this review aims to deepen our understanding of how sleep influences NP, ultimately guiding the development of more effective strategies for managing NP and its associated sleep disturbances to improve the quality of life for those affected.Keywords: neuropathic pain, sleep disturbances, pain pathways, neural circuit